Comparison of Medical Adhesive Tapes in Patients at Risk of Facial Skin Trauma under Anesthesia - Ling Antonia Zeng; Sui An Lie; Shin Yuet Chong (Anesthesiology Research and Practice)
Introduction. Adhesive tapes are used for taping eyelids closed and securing endotracheal tubes during general anesthesia. These tapes can cause facial skin injury. We compared the incidence of facial skin injury and patient satisfaction with different tapes used. Methods. A total of 60 adult patients at risk of skin trauma were randomized to use 3M™ Kind Removal Silicone Tape or standard acrylate tapes: 3M Durapore (endotracheal tube) and Medipore (eyelids). Patients were blinded to tape used. Postoperatively, a blinded recovery nurse assessed erythema, edema, and denudation of skin. Anesthesiologist in charge also assessed skin injury. On postoperative day 1, patients rated satisfaction with the condition of their skin over the eyelids and face on a 5-point Likert scale. Results. More patients had denudation of skin with standard tapes, 4 (13.3%) versus 0 with silicone tape (p=0.026) and in anesthesiologist-evaluated skin injury 11 (37%) with standard versus 1 (3%) with silicone (p=0.002). No significant differences were found in erythema and edema. Patient satisfaction score was higher with silicone tape: over eyelids: mean 3.83 (standard) versus 4.53 (silicone), Mann-Whitney U test, p<0.001; over face: mean 3.87 (standard) versus 4.57 (silicone) (p<0.001). Conclusion. Silicone tape use had less skin injury and greater patient satisfaction than standard acrylate tapes.